Analysis of the Impact of the COVID-19 Pandemic on the Industrial Production Level in Kazakhstan - Mamrayeva, D.G.; Kalinina, O.V.; Tashenova, L.V.; Mukanov, A.L. (BUKETOV BUSINESS REVIEW, 2023)
Object: to analyze the impact of the COVID-19 pandemic on the industrial production level in Kazakhstan. Methods: to pursue this objective, we’ve used statistical data analysis methods, including comparison of output indicators and industrial production indices for the period from 2017 to 2021. Findings: the results of the research have showed that overall industrial production in Kazakhstan decreased during the pandemic. However, the effects of the pandemic on individual sectors varied. Mining and quarrying as well as crude oil and natural gas production experienced significant declines in production due to the shutdown of production capacity for lack of demand in the global energy market. At the same time, other industries, such as food production and agriculture, increased their production capacity amidst increased demand for food. Conclusions: the results of the research have confirmed the hypothesis that the COVID-19 pandemic had a negative impact on the industrial production level in Kazakhstan, causing reduced output and deteriorated financial performance of enterprises. However, we’ve also confirmed the hypothesis that the pandemic spurred development of certain industries in Kazakhstan. Thus, this research allows us to better understand the impact of the COVID-19 pandemic on the economy of Kazakhstan and develop recommendations for its improvement in the future.